1998
DOI: 10.1002/(sici)1097-4601(1998)30:7<463::aid-kin2>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of isatin ring opening in aqueous binary mixtures of methanol and acetonitrile cosolvents

Abstract: Solvent effects on the kinetics of hydrolysis of isatin by sodium hydroxide have been investigated within the temperature range (30-55ЊC) in methanol-water and acetonitrilewater media of varying solvent compositions up to 70% (v/v) of the organic solvent component. The thermodynamic activation parameters were calculated and discussed in terms of solvation effects. The determined isokinetic temperatures, in both systems, revealed the existence of compensation effect arising from strong solute-solvent interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It was also observed that in the presence of ethanol and ethylene glycol the rate of hydrolysis decreases 348 . The effects of other solvents 349 , as well as the photophysics 350 of the hydrolysis reaction of isatin have also been studied.…”
Section: Oxygen Sulfur and Phosphorous Nucleophilesmentioning
confidence: 99%
“…It was also observed that in the presence of ethanol and ethylene glycol the rate of hydrolysis decreases 348 . The effects of other solvents 349 , as well as the photophysics 350 of the hydrolysis reaction of isatin have also been studied.…”
Section: Oxygen Sulfur and Phosphorous Nucleophilesmentioning
confidence: 99%
“…[2][3][4][5] Isatin has special properties due to the fact that it possess many reactive centers, so it undergoes electrophilic aromatic substitution (S E Ar) at carbon atoms on positions five and seven of the phenyl ring., It has been reported that isatin underwent condensation with primary amine and with active methylene compounds such as malononitrile CH 2 (CN) 2 or ethyl cyanoacetate (NCCH 2 COOC 2 H 5 ) on C-3 carbonyl group. 6 Additionally, isatin showed ring opening via nucleophilic attack on C-2 amide group by secondary amine or negatively charge ions such as HO À in which H 2 O must be present, 7,8 or ring expansions as well as spiro-annulations. The rates of hydrolysis of isatins derivatives showed a complex dependence upon pH indicative of subtle changes in mechanisms and rate-limiting step.…”
Section: Introductionmentioning
confidence: 99%